Green Metro Convention Center Performance Building Design in Metro City - Juliansyah A; Ishar S I; Nuzir F A (International Conference on Engineering and Technology Development (ICETD), 2017)
The theater is a building that can accommodate thousands of people were enabled to hold an event of music and theater arts and dance opera large scale. Genre or affect theshape of the stage show and the needs of the audience seats. Besides the need for energy to realize an environmentally friendly building that has been applied to several attemptsnamely, Rainwater harvest and photovaltaic. Tancangan create an architecture that requires a large energy but energy can be reduced or replaced by these technologically. Notforgetting also not forget the architectural design that characterize the city's Metro itself and the use of geometric shapes that respond to environmental conditions